Design of Automatic Car Parking Sensor System Using Arduino Uno Program and HC-SR04 Ultrasonic Sensor - Suriana, I Wayan; Pancane, I Wayan Dikse; Sugarayasa, I Wayan; Adrama, I Nyoman Gede (Open Science and Technology, 2025)
Aims and Methods: One of the challenges that drivers often face when parking a vehicle is limited parking slots. Many drivers face difficulty finding parking slots due to lack of clear information about the slot availability so that they are often forced to make a U-turn after entering a parking lot that turns out to be full. In addition, the limitations of automatic parking systems in conventional vehicles also add to the difficulty in improving parking safety and efficiency, especially in narrow places. This study aims to design and build an automatic car parking sensor system by integrating Arduino-Uno program and HC-SR04 ultrasonic sensor to help drivers by providing accurate and real-time information about the availability of parking slots. The method comprised several stages: hardware designing, consisting of an Arduino Uno microcontroller, HC-SR04 ultrasonic sensor, buzzer, and LED as a warning indicator, then software programming to organize the system logic. The developed system was tested in various scenarios to evaluate both the accuracy of parking slot presence detection and the response speed.Result: The testing results show that the system is able to provide precise warnings according to the detected object in the slot, thus improving safety during the parking process.Conclusion: The Arduino-based car parking sensor system with HC-SR04 ultrasonic sensor could serve as an effective tool in detecting the presence of vehicles in the parking lot.